PENERAPAN MODEL PEMBELAJARAN INKUIRI TERSTRUKTUR BERBANTUAN PHET SIMULATION UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MURID - Firza Riyadhini Yarkasih; Martini, Martini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe students' critical thinking skills. The research design used is a pre-experiment with a one-group pre-test-post-test design technique. The research sample consisted of 38 students from class VIII-C of SMP Negeri 2 Sidoarjo, and the sampling technique used was purposive sampling. The data collection technique in this study was a test. The increase in critical thinking skills using N-Gain obtained a score of 0.7, which is categorized as high. Based on these results, it can be concluded that the application of a structured inquiry model assisted by PhET simulation on the material of vibrations and waves can improve students' critical thinking skills.